Hubungan Antara Self-compassion dan Student Engagement pada Mahasiswa di Sebuah Universitas Negeri di Surakarta - Syifa Syahida Azzahra; Rahmah Saniatuzzulfa (Jurnal Ilmiah Psikologi Candrajiwa, 2025)
Student engagement is considered important because it can influence academic achievement and student success in their studies. Student engagement is a form of student responsibility demonstrated through their compliance with regulations and active participation in the learning process. Student engagement is also positively correlated with the level of self-compassion that students exhibit. Self-compassion enables students to treat themselves with kindness and understanding, increasing their motivation to engage in the learning process and facilitating a more positive approach to dealing with difficulties or failures. The purpose of this study was to investigate whether a relationship exists between self-compassion and student engagement among students. This study involved 385 students from a state university in Surakarta. The sampling method employed was convenience sampling, using the Student Engagement Scale (α = 0.747) and the Self-Compassion Scale (α = 0.879) as instruments. The results of the study, using the product-moment Pearson correlation test, showed that the sig value was 0.000 and the r value was 0.402, indicating a significant relationship between self-compassion and student engagement among students. The implications of these results are the importance of developing self-compassion skills in students, as an increase in self-compassion can help them manage academic stress, enhance learning motivation, and encourage more active involvement in both academic and non-academic activities.